Manajemen Public Relations Pendidikan Islam (Kajian Tematik Al Qur’an Dan Al Hadits) - Dian Iskandar Jaelani (Tarbiyah Departement collaboration with AMCA, 2014)
Public Relations (PR) has two senses. First, in terms of public relations as communication techniques. And second, public relations as a method of communication. The concept of Public Relations with respect to understanding through knowledge creation activities, and through these activities that impact the changes will appear. Public Relations itself is a combination of various immunization and included in the ranks of the social sciences such as political science, economics, history, psychology, sociology, communication and others.